School tracking and intergenerational social mobility - Tuomas Pekkarinen (IZA World of Labor, 2014)
The goal of school tracking (assigning students to different types of school by ability) is to increase educational efficiency by creating more homogeneous groups of students that are easier to teach. However, there are concerns that, if begun too early in the schooling process, tracking may improve educational attainment at the cost of reduced intergenerational social mobility. Recent empirical evidence finds no evidence of an efficiency–equality trade-off when tracking is postponed.
Keywords: J62; I24; 330; tracking; intergenerational mobility; educational attainment